1992
DOI: 10.1103/physrevlett.69.578
|View full text |Cite
|
Sign up to set email alerts
|

Electric charges of positrons and antiprotons

Abstract: Tests of the electric charges carried by the positron and antiproton are derived from recent measurements of the cyclotron frequencies of these particles, and from the spectroscopy of exotic atoms in which they are constituents.There has recently been considerable interest in highprecision tests of the equality of particle and antiparticle masses that is required by CPT symmetry [1,2]. A method that has been applied to electrons and positrons [3] and protons and antiprotons [l] utilizes the cyclotron frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…These methods seem out of the question for antiprotons, although an atomic-beam experiment has been suggested that has something in common with both (1) and (3) Deutch, 1992). A beam of antihydrogen atoms would be injected between the plates of a parallel-plate capacitor.…”
Section: Direct Measurement Of Charge-bulk Matter Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods seem out of the question for antiprotons, although an atomic-beam experiment has been suggested that has something in common with both (1) and (3) Deutch, 1992). A beam of antihydrogen atoms would be injected between the plates of a parallel-plate capacitor.…”
Section: Direct Measurement Of Charge-bulk Matter Methodsmentioning
confidence: 99%
“…(22) is small. The deflection of the beam is given by (Deutch, 1992) (Geer et al, 1994). From experiment T861 at Fermilab.…”
Section: Direct Measurement Of Charge-bulk Matter Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several example comparisons include: electron/positron mass [3], charge [4], and gyromagnetic ratio [5];…”
Section: Precision Comparison Of the Properties Of Hydrogen And Antihmentioning
confidence: 99%
“…B.1(c)). The total depletion width, w, is given as (assuming that potential due to charge diffusion is small) [110], 4) where V b is the reverse bias applied, is the dielectric constant of the medium (11.9 for silicon), and N a and N d are the acceptor and donor concentrations, respectively. For example, with doping concentrations of N a = N d = 10 13 cm −3 and an applied reverse bias of V b = 65 V, the depletion width is w 300 µm.…”
mentioning
confidence: 99%